Y= a(x-3)^2+6
2= a(0-3)^2+6
2=a(-3)^2+6
2=a(9)+6
2-6=9a
-4=9a
-4/9=a
Therefore the equation in vertex form is
y = -4/9 (x-3)^2+6
Answer: im not sure
Step-by-step explanation:
Answer:
5x=13.5
Step-by-step explanation:
Well, we know that 1x=2.7. So, if we want 5x we need to multiply 2.7*5 becuase 1x=2.7, so 5x=2.7*5.
Multiply. 2.7*5=13.5
So, 5x=13.5.
Hope this helps!
Answer:
65
Step-by-step explanation:
they're going by 5s every time her score increases. hope I helped (:
F(x)=2x^2-x-6
Factoring:
f(x)=2(2x^2-x-6)/2=(2^2x^2-2x-12)/2=[(2x)^2-(2x)-12]/2
f(x)=(2x-4)(2x+3)/2=(2x/2-4/2)(2x+3)→f(x)=(x-2)(2x+3)
g(x)=x^2-4
Factoring
g(x)=[sqrt(x^2)-sqrt(4)][sqrt(x^2)+sqrt(4)]
g(x)=(x-2)(x+2)
f(x)/g(x)=[(x-2)(2x+3)] / [(x-2)(x+2)
Simplifying:
f(x)/g(x)=(2x+3)/(x+2)
Answer: Third Option (2x+3)/(x+2)